Reliability of Center of Pressure Parameters in Postural Sway among Athlete and Non-athlete Men in Different Levels of Fatigue and Vision - Zohreh Meshkati; Mehdi Namazi-Zadeh; Mahyar Salavati; Masoud Mazaheri (University of Social Welfare and Rehabilitation Sciences, 2010)
Objective: This study aimed to investigate the skill, fatigue and vision-related differences between athletes and non-athletes in reliability of center of pressure (COP) measures derived from force platform. Materials & Methods: Thirty-one healthy male participants (15 athletes and 16 non-athletes) were tested on force platform on two sessions with a 48-72 hr interval. COP parameters was recorded during two-legged quiet standing before and after a generalized fatigue exercise by treadmill, with eyes-open (EO) and eyes-closed (EC). Standard deviation (SD) of amplitude, SD of velocity in anteroposterior (AP) and mediolateral directions and mean total velocity were calculated from 30 sec COP data. Results: Higher intraclass correlation coefficient (ICC) was found for COP measures in the athlete (compared with the non-athlete) group. ICC was increased in post-fatigue (compared with pre-fatigue) conditions. Also higher ICC was found for EC (compared with EO) tests. Coefficients of variation smaller than 15% were obtained for most of the COP measures. Alpha level of 0. 05 was considered for all statistical analyses. Regarding the level of skill, fatigue and vision, mean total velocity (P=0. 001) and SD of velocity (AP) (P=0. 001) were the most reliable parameters. Conclusion: The results aid researchers in selection of reliable COP measures for future studies of postural control in sports. In this way, researchers can use mean total velocity and SD of velocity (AP) parameters in their studies in same conditions on athletes.